ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT SEKTOR PUBLIK - Stefhany, Patrisia; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine some factors which influence public sector audit quality at the Audit Board of the Repbulic of Indonesia East Java Province representative. The variables in this research are accountability, due professional care, auditor ethics, work experience,and knowledge. Quantitave method has been applied in this research. The data collection method is done by giving written question to the respondents. The data is the primery data which has been obtained by issuing quesionnaires to the respondents. The population in this research is all auditors who have been working at the Audit Board of the Republic of Indonesia East JavaProvince representative. The sample selection has been done by using purposive sampling method and 50 auditors have been selected as samples. The analysis technique has been done by using multiple liniear regressions analysis and the SPSS. The result of the research shows that variables i.e., accountability give positive influence to the public sector quality, due professional care give positive influence to the public sector quality, auditor ethics give positive influence to the public sector quality, work experience give positive influence to the public sector quality,and knowledge give positive influence to the public sector audit quality.Keywords: Accountability, due professional care, auditor ethics, work experience, public sector audit quality